Karakteristik Beton dengan Variasi Diameter Serat Bambu terhadap Kuat Tarik Belah Beton - Febryandi Alfuadi; Marguan Fauzi; Khodijah Al Qubro; MIftahul Jannah Lubis (Universitas Batanghari Jambi, 2026)
Concrete is a construction material with high compressive strength; however, it has a relatively low tensile strength, which makes it susceptible to cracking. One approach to improving the tensile strength of concrete is the addition of natural fibers, such as bamboo fibers, which are environmentally friendly, lightweight, and easily obtained. Variations in bamboo fiber diameter may influence the bonding between the fibers and the concrete matrix, thereby affecting the splitting tensile strength of concrete. This study aims to analyze the effect of bamboo fiber diameter variations on the splitting tensile strength of concrete and to determine the fiber diameter that produces the highest average splitting tensile strength. The research method used is an experimental laboratory method with a designed concrete strength of f’c 25 MPa. The bamboo fiber diameters used in this study were 2 mm, 4 mm, and 6 mm. Cylindrical specimens with dimensions of 100 mm × 200 mm were used and tested at the ages of 7, 14, 21, and 28 days. The results of this study indicate that the addition of bamboo fibers improves the splitting tensile strength of concrete. At 28 days, the control concrete had a splitting tensile strength of 2.65 MPa, while concrete with bamboo fiber additions showed values of 2.77 MPa for 2 mm diameter, 3.24 MPa for 4 mm diameter, and 2.94 MPa for 6 mm diameter. Based on the average test results, the 4 mm fiber diameter showed the highest splitting tensile strength compared with the 2 mm and 6 mm variations. This study recommends the use of 4 mm bamboo fiber as an environmentally friendly alternative additive to improve the tensile performance of concrete and support sustainable construction development.